Kajian Poster Film Tim Burton dan Perannya dalam Pembentukan Identitas Autoral - Laila Rahmawati; M Rahman Athian (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This research analyses five film posters by Tim Burton, including The Nightmare Before Christmas, Sleepy Hollow, Corpse Bride, Sweeney Todd: The Demon Barber of Fleet Street, and Frankenweenie, to explore how recurring visual symbols contribute to the formation of the director’s distinctive artistic identity. Employing a qualitative methodology alongside Roland Barthes’s semiotic theory, the posters were examined through the levels of denotation and connotation, with particular attention to visual elements such as colour, composition, typography, and iconography. The findings reveal four prevalent visual motifs that consistently appear across the selected posters: the full moon, muted and desaturated colour schemes, fragmented or flawed bodies, and marginalised protagonists. Collectively, these recurring elements construct the cultural myth of the “Burtonesque” aesthetic, which extends beyond individual films, genres, and narrative contexts. The research also identifies a transition in the marketing approach, shifting from an emphasis on Burton’s identity and reputation as a distinctive filmmaker toward greater attention to his previous commercial achievements. Overall, this study demonstrates that film posters function not merely as promotional materials but also as visual texts that actively construct and communicate a director’s authorial identity by integrating auteur theory with Barthesian semiotics.